PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN MASYARAKAT PADA RUMAH SAKIT UMUM DAERAH BADUNG - Lakmi, Ade Rosita (CITIZEN CHARTER, 2014)
ABSTRACT Badung hospital is a government hospital in Bali and its trying give good health service for its public but still has found several complaints at health service given. This study aims to find out the effect of service quality to the public satisfaction level at the Badung hospital. This research type was correlation analytic. Sampling was by proportionate stratified random sampling by number of 60 respondents. Data collection by using questioner. Data analysis technique by using simple regression method. The result showed there is significant effect of service quality to the public satisfaction level at Badung hospital with equation Y = 9,938 + 0,379X. correlation value (r) = 0,399Â  and level of service quality effect to the public satisfaction levelÂ  is 12,9%. Keywords: Service Quality, Satisfaction, Public.